Jawabanmu

2014-09-09T19:41:25+07:00
Menyamakan penyebutnya

 \frac{4}{x+3} - \frac{5}{x-1} = \frac{4.(x-1)}{(x+3)(x-1)} - \frac{5.(x+3)}{(x+3)(x-1)}
                      =\frac{(4x-4)-(5x+3)}{(x+3)(x-1)}
                     = \frac{4x-4-5x-3}{ x^{2} -x+3x-3}
                     = \frac{-x-7}{ x^{2} +2x-3}

Sama kyk di atas

\frac{3}{2x+5} + \frac{2 }{6 x^{2} +7x-20}= \frac{3}{2x+5} + \frac{2}{6 x^{2} +7x-20}

                                      = \frac{3.(6 x^{2} +7x-20)}{(2x+5)(6 x^{2} +7x-20)} + \frac{2.(2x+5)}{(2x+5)(6 x^{2} +7x-20)}

                                      = \frac{(18 x^{2} +21x-60)+(4x+10)}{(2x+5)(6 x^{2} +7x-20)}

                                      = \frac{18 x^{2} +25x-50}{(2x+5)(6 x^{2} +7x-20)}

Ini juga sama


bisa di sederhanain lagi gak? mksh
MAAF LG DI EDIT
KEPENCET
mksh